ACCOUNTING INFORMATION SYSTEM PERFORMANCE ANALYSIS - Tenriwaru Tenriwaru; Nilam Salam (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2021)
Purpose – This study aims to determine the performance of accounting information systems at PT. Bumi Jasa Utama. Design/methodology/approach – The analytical method used is a narrative analysis method with a descriptive qualitative approach to find out how the performance of the accounting information system at the company PT. Bumi Jasa Utama. Findings – The results of the study found that the current performance of the accounting information system at the company PT. Bumi Jasa Utama shows that the company's information system has been used properly. Originality – The data of this study were obtained from primary data and secondary data with data collection techniques through observation, interviews, documentation, and literature studies as well as testing the validity of the data based on triangulation of sources, techniques, and time conducted at PT. Bumi Jasa Utama. Keywords: Accounting Information System Performance, Accounting Information System Paper Type Research Result